Evaluasi Kurikulum - Rusmani, Muhammad Afdal; Arifmiboy, Arifmiboy (ANTHOR: Education and Learning Journal, 2023)
Evaluation is part of the management system, namely planning, organizing, implementing, monitoring, and evaluating. The curriculum is also designed from the stages of planning, organizing, implementing and finally monitoring and evaluating. Without evaluation, it will not be known how the curriculum conditions in the design, implementation, and results. This research uses the method (literature review) by exploring various references related to the implementation of educational curriculum evaluation development. Curriculum evaluation is carried out based on certain objectives so that the implementation of the evaluation can be directed and right on target. This paper will discuss the definition of curriculum evaluation, curriculum evaluation models, what are the objectives of curriculum evaluation and who are the curriculum evaluators.